A comparison of the misconceptions about the time-efficiency of algorithms by various profiles of computer-programming students - ÖZDENER DÖNMEZ, NESRİN (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This study focuses on how students in vocational high schools and universities interpret the algorithms in structural computer programming that concerns time-efficiency. The targeted research group consisted of 242 students from two vocational high schools and two departments of the Faculty of Education in Istanbul. This study used qualitative and quantitative research methods together. During the study the students were asked to evaluate the algorithms given to them in terms of their run-time efficiency. The analysis of the data has used descriptive statistics and the results of the independent sample T-tests to compare the groups. The findings of this study slightly stress that the students have misconceptions about algorithms. Students in high schools and in computer education and instructional education departments have the same observed misconceptions, while mathematics education students are better at interpreting the misconceptions. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: algorithms; time-efficiency; misconceptions; SCIENCE